I've been tasked with using the fitch proof system to do the to complete the following proof: Given ¬q, (¬p⇒(¬q⇒¬r)), (s∨r), (s⇒t), and (p⇒t), prove t. I'm experiencing difficulty getting this done. I've tried by assuming ¬t, proving a contradiction and thereby deriving ¬¬t, and then using negation elimination to get t. I've also tried to prove r⇒t and then use or elimination to prove t. I have unfortunately not yet been able to prove t using these approaches. If anyone has any ideas for how I may go about solving this proof, I'd appreciate your sharing them with me.
-
$\begingroup$ You have premises $s \to t$ and $p \to t$; thus, in order to prove $t$, we have to derive either $s$ or $p$. From premise $s \lor r$ by Disjunction Elim one sub-proof gives us $s$ and it's fine. Now we have to work with the other sub-proof, starting with $r$, in order to derive either $s$ or $p$. This one is a little bit tricky... $\endgroup$– Mauro ALLEGRANZAMay 30 at 13:30
-
$\begingroup$ Question for clarification: What rules do you have, in particular do you have Disjunctive Syllogism or LEM? $\endgroup$– Andrew LMay 30 at 19:46
-
$\begingroup$ Andrew L, thank you for trying to help me. I'm able to use the following rules: Reiteration, Negation introduction, Negation elimination, And introduction, And elimination, Or introduction, Or elimination, Assumption, Implication elimination, Biconditional introduction, Biconditional elimination, Universal introduction, Universal elimination, Existential introduction, Existential elimination. $\endgroup$– JCKing87May 31 at 11:47
3 Answers
Probably the easiest way forward is to assume $P$ and derive $T$, then assume $\neg P$ and derive $T$. Both of these derivations are straightforward. From there, depending on your exact rules, you should be able to extract $T$ by itself.
I think this is the easiest way to go about proving it pseudo-Fitch Style:
- $\neg q$ (Assumption)
- $\neg p \to (\neg q \to \neg r)$ (Assumption)
- $s \lor r$ (Assumption)
- $s \to t$ (Assumption)
- $p \to t$ (Assumption)
- $r$ (Hypothesis)
- $\neg t$ (Hypothesis)
- $p$ (Hypothesis)
- $t$ (5,8 $\to$ Elim)
- $\bot$ (7,9 $\bot$ Intro)
- $\neg p$ (8-10, $\neg$ Intro)
- $\neg q \to \neg r$ (2,11 $\to$ Elim)
- $\neg r$ (1,12 $\to$ Elim)
- .
- .
- $r \to t$ (6-15 $\to$ Intro)
- $t$ (3,4,16 $\lor$ Elim)
I left some of it to fill in since I think that’s probably the trickiest part.
I've tried by assuming ¬t, proving a contradiction and thereby deriving ¬¬t, and then using negation elimination to get t. I've also tried to prove r⇒t and then use or elimination to prove t.
Combine both these approaches. Assume $\lnot t$ and then use $\vee$-elimination on $(s\vee r)$ where you derive contradictions in each case.
$\def\fitch#1#2{\quad\begin{array}{|l}#1\\\hline#2\end{array}} \fitch{~~1.~~¬q\\~~2.~~(\lnot p\to(\lnot q\to\lnot r))\\~~3.~~(s\vee r)\\~~4.~~(s\to t)\\~~5.~~(p\to t) }{\fitch{~~6.~~\lnot t}{\fitch{~~7.~~s}{~~~~\vdots\\~~\mathrm h.~~\bot}\\\fitch{~~\mathrm i.~~r}{~~~~\vdots\\~~\mathrm j.~~\lnot r\\~~\mathrm k.~~\bot}\\~~\ell.~~\bot}\\~~\mathrm m.~~\lnot\lnot t\\~~\mathrm n.~~t}$